The angle of incidence of Paul Roux's catechism - a study on the theology of a French refugee at the Cape - V. E. d'Assonville (Acta Theologica)
With the Belijdenis of Paul Roux we have an indigenous document of early eighteenth century theological reflection among some French refugees of the first generations at the Cape. It provides us with useful opportunities to analyse the theology of an important part of the history of the Huguenots. In this study, attention is given to the matter of the introductory question of this catechism book with regard to its importance as well as its content. It is argued that the angle of incidence of this catechism is pointing to a shift away from the reformed heritage towards the Aufklärung and Rationalism. Whether this applies to the rest of the Belijdenis in its entirety is not object of this analysis, though.